Projection of the clinical and economic burden of chronic kidney disease between 2022 and 2027 in Spain: Results of the Inside CKD project - Juan F. Navarro González; Alberto Ortiz; Ana Cebrián Cuenca; Marta Moreno Barón; Lluís Segú; Belén Pimentel; Unai Aranda; Blanca Lopez-Chicheri; Margarita Capel; Elisenda Pomares Mallol; Christian Caudron; Juan José García Sánchez; et al. (Nefrología (English Edition))
Background and objective: Chronic kidney disease (CKD) is a growing health problem affecting between 10% and 15% of the Spanish population. The lack of updated projections of the evolution of the disease burden hinders the development of evidence-based health policies and interventions to optimise the management of the disease and prevent its progression. The aim of this study is to project the evolution of the clinical and economic burden of CKD in Spain between 2022 and 2027. Materials and methods: Inside CKD uses a validated microsimulation approach to project the burden of CKD. The projection is based on a virtual population according to Spanish demographics, literature, national data registries and clinical expert opinion. Costs associated with CKD management, renal replacement therapy (RRT), cardiovascular complications and arterial comorbidities were included. Results: In Spain, an absolute increase in the prevalence of CKD of 1% (from 10.7% to 11.7%) is expected between 2022 and 2027, corresponding to an increase from 5.14 million to 5.68 million patients in 2027. However, only one third of CKD patients would be diagnosed. Of these diagnosed patients, 3.9% will require RRT in 2027, an increase of 14.7% from 2022. A total of 654,281 accumulated deaths are expected in patients with CKD diagnosed between 2022 and 2027. The economic burden of diagnosed CKD is expected to increase by 13.8% to 4.89 billion euros in 2027, representing 5.56% of total Spanish public health expenditure in 2027 (compared to 4.88% in 2022), of which 42.5% will be allocated to RRT (2.4% of public health expenditure). Conclusions: The Inside CKD project highlights the growing clinical, economic and social burden of CKD in Spain expected by 2027. Progression to more advanced stages with the need for RRT and associated complications represent a small proportion of the total CKD population, but contribute significantly to overall costs. Resumen: Antecedentes y objetivos: La enfermedad renal crónica (ERC) es un problema de salud creciente que afecta entre el 10–15% de la población española. La escasez de proyecciones actualizadas sobre la evolución de la carga de enfermedad obstaculiza el desarrollo de políticas e intervenciones sanitarias basadas en la evidencia para optimizar el manejo de la enfermedad y prevenir su progresión. El objetivo de este estudio es proyectar la evolución de la carga clínica y económica de la ERC en España entre 2022 y 2027. Materiales y métodos: Inside CKD utiliza un enfoque de microsimulación validado para analizar la carga proyectada de la ERC, a partir de una población hipotética según la demografía española, bibliografía, registros de datos nacionales y opinión de expertos clínicos. Los costes incluidos fueron asociados a la gestión de la ERC, el tratamiento renal sustitutivo (TRS), las complicaciones cardiovasculares y las comorbilidades arteriales. Resultados: En España, se prevé un incremento absoluto en la prevalencia de ERC del 1% (del 10,7% a 11,7%) entre 2022 y 2027, equivalente a un aumento de 5,14 a 5,68 millones de pacientes en 2027, de los cuales solo un tercio serían diagnosticados. Se prevé un total de 654.281 muertes acumuladas en pacientes con ERC diagnosticada entre 2022 y 2027. El 3,9% de los pacientes diagnosticados requerirán TRS en 2027, un incremento del 14,7% respecto a 2022. La carga económica de la ERC diagnosticada se prevé que aumente un 13,8%, hasta los 4.890 millones de euros en 2027, lo que representaría un 5,56% del gasto sanitario público español total en 2027 (frente a 4,88% en 2022), de los cuales el 42,5% se destinará a TRS (2,4% del gasto sanitario público). Conclusiones: El proyecto Inside CKD demuestra la creciente carga clínica, económica y social de la ERC en España prevista para el 2027. La progresión a los estadios más avanzados con necesidad de TRS y las complicaciones asociadas representan una pequeña parte de la población total con ERC, pero contribuyen de forma significativa a los costes totales.